Determination of Impact Force History during Multicolumn Barge Flotilla Collisions against Bridge Piers - Luperi, Francisco José (2013)
The collision of barge flotillas against bridge piers is a design scenario that often controls the design of bridges that span navigable waterways. Current design approaches vary significantly in their assumptions and mostly rely on design code guidelines. The influence of adjacent barge columns on multicolumn flotilla impacts is not well established in the literature; some design codes ignore the effects of adjacent barge columns, assuming they break away upon impact, whereas others assume full contribution. The actual contribution of adjacent barge columns has a major influence on the amount of energy absorbed by the impacted structure and, therefore, on the load history attributable to the impact. The behavior of barge flotillas during impact depends upon several factors, such as configuration of flotilla, impact speed, barge bow-crushing behavior, and dynamic response of pier. This paper presents a simplified procedure that allows the estimation of the impulse delivered by the adjacent barge columns for head-on impacts. The proposed simplified procedure is based on a parametric study performed by means of a multidegree-of-freedom, two-dimensional model described in this paper. The proposed model is able to account for nonlinear interaction between barges, nonlinear barge bow behavior, and dynamic structural response. The proposed procedure allows for an improved estimation of impact load histories attributable to the collision of barge flotillas.